VERTEBRATES AS POTENTIAL DISPERSERS OF PALM TREES IN AN URBAN ENVIRONMENT - FERNANDES, Leandro Siqueira (2019)
Palm trees are important resources for many species of animals, which when consumed the fruits promote the movement of the seeds. Palm trees of the genus Attalea and Astrocaryum are often abundant in forest fragments. However, little is known about animals that consume their fruits. The objective of this work was to identify the animals that consume fruits of Attalea maripa and Astrocaryum aculeatum. The study was carried out in the forest fragment of (UFAM), in Manaus, Brazil. The observations were made from July to September / 2018 with the help of binoculars, camera traps and photographic. The camera traps were installed in an A. aculeatum tree and eight A. maripa trees for 24 hours. In general, 11 species of animals (primates, rodents, marsupials and birds) feeding on the fruits. The seeds were consumed near the mother trees. No predated seeds were found. The mammals corresponded to the majority (72.73%) of the animals that consumed the fruits. On the other hand, despite the minority (27.27%), birds also use such resources. Most of the large potential dispersers no longer exist in the UFAM fragment, but the representatives identified in the work benefit and play the fundamental role for the dispersion of fruits.